2016
DOI: 10.3389/fnhum.2016.00417
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Courses of Phonological and Orthographic Encoding in Handwritten Production in Chinese: An ERP Study

Abstract: A central issue in written production concerns how phonological codes influence the output of orthographic codes. We used a picture-word interference paradigm combined with the event-related potential technique to investigate the temporal courses of phonological and orthographic activation and their interplay in Chinese writing. Distractors were orthographically related, phonologically related, orthographically plus phonologically related, or unrelated to picture names. The behavioral results replicated the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
8
1
Order By: Relevance
“…Our finding of earlier access to phonology than to orthography in written production is in agreement with our earlier results from purely behavioral results (e.g., Qu, Damian, Zhang, & Zhu, 2011) summarized in the Introduction. However, this pattern contrasts with both behavioural and EEG results (Zhang & Wang, 2016) in which relatively late phonological effects were found. Here we consider possible reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding of earlier access to phonology than to orthography in written production is in agreement with our earlier results from purely behavioral results (e.g., Qu, Damian, Zhang, & Zhu, 2011) summarized in the Introduction. However, this pattern contrasts with both behavioural and EEG results (Zhang & Wang, 2016) in which relatively late phonological effects were found. Here we consider possible reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Path analysis is confirmatory in nature, and it should be based on certain theoretical frameworks or research findings (Klein, 2010;McDonald & Ho, 2002). Drawing on the findings about the influence of L1 background on phonological awareness (Branum-Martin, Tao, & Garnaat, 2015;Zhang, 2017) and the correlation matrix (Table 8) between the measured variables in our study, only L1 background and gender, out of the four background variables, were included in the model.…”
Section: Resultsmentioning
confidence: 96%
“…According to the orthographic autonomy hypothesis, phonological information is not necessarily activated in order to access the orthographic code in the task of spelling (Rapp, Benzing, & Caramazza, 1997). The independent role of orthographic information in facilitating written production has been observed in Chinese characters (Han, Zhang, Shu, & Bi, 2007;Law, Yeung, Wong, & Chiu, 2005;Zhang & Wang, 2016). Phonetic radical awareness is just one part of orthographic awareness of characters, and by itself might not be able to activate the orthographic representation of the compound character for CSL learners with limited L2 proficiency.…”
Section: Chinese Character Writingmentioning
confidence: 99%
“…Over the past decade, researchers have studied the cognitive neural mechanisms of written production using brain imaging techniques. As a result, the brain regions underlying the various cognitive processes involved in written production have been elucidated (e.g., Dufor & Rapp, 2013; Planton et al., 2013; Purcell, Napoliello, et al., 2011; Purcell & Rapp, 2013; Rapp & Dufor, 2011; Rapp & Lipka, 2011), and the time course of some of these processes has been investigated (e.g., Baus et al., 2013; Perret & Laganaro, 2012; Python et al., 2018; Qu et al., 2016; Zhang & Wang, 2016). However, to date, no studies have investigated neural oscillation in relation to written production, and this gap in the literature is the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Existing electrophysiological studies have provided fine‐grained temporal information about the different components of language production (e.g., Aristei et al., 2011; Costa et al., 2009; Python et al., 2018; Qu et al., 2012; Wang et al., 2018; Zhang & Wang, 2016; for reviews, see Ganushchak et al., 2011; Indefrey, 2011). However, only a few of these studies have explored neural oscillations involved in speech production (Ewald et al., 2012; Hendrix et al., 2017; Piai, Roelofs, & Maris, 2014; Piai et al., 2012), and no study has reported neural oscillations related to written production.…”
Section: Introductionmentioning
confidence: 99%